2007
DOI: 10.1111/j.1365-2966.2007.12240.x
|View full text |Cite
|
Sign up to set email alerts
|

Australia Telescope Compact Array 1.2-cm observations of the massive star-forming region G305.2+0.2

Abstract: We report on Australia Telescope Compact Array observations of the massive star‐forming region G305.2+0.2 at 1.2 cm. We detected emission in five molecules towards G305A, confirming its hot core nature. We determined a rotational temperature of 26 K for methanol. A non‐local thermodynamic equilibrium excitation calculation suggests a kinematic temperature of the order of 200 K. A time‐dependent chemical model is also used to model the gas‐phase chemistry of the hot core associated with G305A. A comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 31 publications
2
42
1
Order By: Relevance
“…The 25‐GHz maser was found to be 3 arcsec to the east from the position of the 6.7‐GHz maser 305.202+0.208 (G305B region). It is worth noting that Walsh et al (2007) also detected 25‐GHz emission (several transitions of the series) towards two other locations in this source: near G305A and the south‐eastern H ii region. However, the radial velocity and a clear maser appearance of the feature near G305B allows an unambiguous identification of the suspected 9.9‐GHz maser with this position, near the 6.7‐GHz maser 305.202+0.208.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The 25‐GHz maser was found to be 3 arcsec to the east from the position of the 6.7‐GHz maser 305.202+0.208 (G305B region). It is worth noting that Walsh et al (2007) also detected 25‐GHz emission (several transitions of the series) towards two other locations in this source: near G305A and the south‐eastern H ii region. However, the radial velocity and a clear maser appearance of the feature near G305B allows an unambiguous identification of the suspected 9.9‐GHz maser with this position, near the 6.7‐GHz maser 305.202+0.208.…”
Section: Resultsmentioning
confidence: 59%
“…This most likely implies that markedly different physical conditions exist in this particular source. One may speculate that this might be related to another peculiarity found by Walsh et al (2007): the high‐mass star‐forming region associated with G305B is bright in infrared, old according to the chemistry, but has no H ii region sufficiently developed to be detectable. The expansion of an H ii region could be hindered because of the dense environment and/or by continuing infall of the matter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations with Mopra in Walsh & Burton (2006) showed that many detected lines peak at the site of G305A, with weaker emission associated with G305B. As discussed in Walsh et al (2007), Steve Longmore (private communication) has detected the NH 3 (4,4) line in G305A which requires a temperature of at least 100 K, strongly suggesting that G305A is a hot core. In Walsh et al (2007), a hot core chemical model based on the physical conditions of G305A was used to compare the observed column densities of a number of species.…”
Section: Introductionmentioning
confidence: 93%
“…There is an H ii region some 10 to the southwest (Walsh et al 2007), but the infrared source itself is not associated with centimeter free-free emission (Phillips et al 1998;Walsh et al 2007). The extrapolated IRAS luminosity is > ∼ 10 5 L (Walsh et al 2001), which together with the cm non-detection supports our view that this object is a MYSO in a pre-UCH ii-region stage.…”
Section: G30520+021mentioning
confidence: 99%